A study on entrepreneurial attitudes of upcountry vegetable farmers in Sri Lanka. Issue 1 (16th May 2016) - Rosairo, H. S. Rohitha; Potts, David J.
Abstract : Purpose: – The purpose of this paper is to investigate the entrepreneurial attitudes of upcountry vegetable farmers in Sri Lanka with respect to the characteristics of innovation, opportunity seeking and risk taking and considers their implications for rural development efforts. Design/methodology/approach: – The study was carried out in the hilly areas of the Badulla district in the Uva Province of Sri Lanka. Primary data were collected through a survey using a researcher-administered questionnaire as the data collection instrument and the individual farmer as the unit of analysis. Findings: – Most vegetable farmers in the upcountry areas were found to be attitudinally entrepreneurial. Entrepreneurial attitudes were determined more by educational background and farming experience than age, gender, extent of farmland, type of farming and ownership of farmland. Farming experience related positively with innovation, opportunity seeking and risk taking, but farmers' educational background showed no significant association with innovation. Research limitations/implications: – It is suggested that farmer-owned companies with appropriate institutional arrangements could reduce transaction costs for buyers, and introduce accessible rural finance schemes to enhance provision of assets and technology. Such a rural setting would gain from initiatives on marketing alternatives and entrepreneurial skill development. Future research could benefit from analysis of the financial and social performance and entrepreneurial skills of vegetable farmers. Originality/value: – The entrepreneurial attitude of farmers is an under-researched area of study particularly in the Sri Lanka context. Rural development initiatives could target entrepreneurial farmers based on these criteria to achieve maximum production impact. However care needs to be taken to consider the potential distributive impact of such targeting on farmers regarded as non-entrepreneurial.